A wandering Galilean : essays in honour of Seán Freyne - Daly-Denton, Margaret.; Fitzpatrick-McKinley, Anne.; Freyne, Seán.; Rodgers, Zuleika. (Supplements to the Journal for the Study of Judaism, 2009)
Starting his career as a scholar of the New Testament, Seán Freyne's work became synonymous with the study of Galilee in the Greek and Roman periods. His search for a deeper and more nuanced understanding of Judaism in the Greek and Roman periods and the development of the early Christian movement has led him to interface with scholars in many related disciplines. In order to do justice to the breadth of Seán Freyne's interests, this volume includes contributions from scholars in the fields of Archaeology, Ancient History, Classics, Hebrew Bible, Early Judaism, Rabbinic Judaism, Early Christianity, New Testament, and Medieval Judaism. The resulting volume demonstrates not only the honoree's interdiciplinary interests, but also the interconnectedness of these disciplines.